FRESHNESS CHANGES OF YELLOWFIN TUNA (Thunnus albacares) DURING STORAGE AT LOW TEMPERATURES - Tri Winarni Agustini (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Freshness quality is considered as an important factor in determining overall quality of particular fish product items. The degree to which the freshness quality of the items meets the consumer’s expectation concerning freshness quality will greatly affect whether the fisheries product item will be purchased again or not. Considering the importance of fish freshness quality, many methods have been proposed to evaluate fish freshness including physical, chemical and sensory methods. The K value is one of the chemical methods widely used , especially in Japan, as a fish freshness index to evaluate the quality change of raw fish. Tuna has been regarded as a palatable and valuable fish species and its freshness is the concern of many researchers. This study is aimed at investigating the freshness change of yellowfin tuna (Thunnus albacares) during storage at low temperatures (10oC, 5oC and 0oC) by measuring the K value of the fish. Observation on the changes of ATP and its related compounds during storage was also carried out. The result of the study shows that the freshness of yellowfin tuna as measured by K value, changed in different patterns depending on the storage temperatures. The higher the temperature of storage the faster was the decrease in freshness of yellowfin tuna. It was also observed that yellowfin tuna could be eaten raw up to 1 day, 2 days and 4 days storage at temperature of 10º C, 5º C and 0º C, respectively. Storage temperature of 0º C is recommended for its preservation in chilled state. The use of HPLC allows for each of ATP-related compounds to be determined quantitatively.The Ki value is more appropriate for measuring fish freshness obtained more than 24 hours after death